External carotid stenting for symptomatic stenosis in a patient with patent EDAS for Moyamoya disease. (1st August 2014) - Schmidt, Eric; Parker, Lindsey; Fraser, Justin F
Abstract : Background: Moyamoya disease is characterized by progressive narrowing of the internal carotid artery (ICA). Symptomatic patients typically undergo cerebrovascular intervention via extracranial–intracranial (EC–IC) bypass, most often with the use of the superficial temporal artery. This case of Moyamoya disease is of particular interest as the patient presented with a unilateral atherosclerotic external carotid artery (ECA) stenosis after EC–IC bypass that eliminated the benefit of his original surgery, resulting in a symptomatic presentation. Clinical presentation: A 53-year-old man presenting with Moyamoya disease and known left ICA occlusion had received a bilateral encephaloduroarteriosynangiosis (EDAS) bypass 10 years previously. He re-presented complaining of right-sided tingling, weakness, and numbness radiating up the arm. CT angiography indicated significant stenosis of the left ECA. ECA angioplasty and stenting with a distal protection device resulted in resolution of his symptoms. Conclusions: This case illustrates that a patient presenting with Moyamoya disease and concurrent symptomatic ECA stenosis post-EDAS can be effectively and safely treated with ECA stenting.